Research of functional properties of nitride ion-plasma coatings - Vaulina O. Yu. Olga Yurievna; Ovechkin B. B. Boris Borisovich; Papchenko A. V.; Shvagrukova E. V. Ekaterina Vasilevna (2016, 2016)
Title screen